2006
DOI: 10.1093/nar/gkl580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of human Formula: the role of modified bases in mRNA recognition

Abstract: Accuracy in translation of the genetic code into proteins depends upon correct tRNA–mRNA recognition in the context of the ribosome. In human tRNAUUULys,3 three modified bases are present in the anticodon stem–loop—2-methylthio-N6-threonylcarbamoyladenosine at position 37 (ms2t6A37), 5-methoxycarbonylmethyl-2-thiouridine at position 34 (mcm5s2U34) and pseudouridine (ψ) at position 39—two of which, ms2t6A37 and mcm5s2U34, are required to achieve wild-type binding activity of wild-type human tRNAUUULys,3 [C. Yar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 74 publications
0
49
0
Order By: Relevance
“…Previous molecular dynamics modeling and NMR spectrometry experiments had indicated that lengthy modifications at position-5 of U's could freeze the conformation of the nucleotide and dictate the hydrogen bonding geometry Durant et al 2005;McCrate et al 2006;Weixlbaumer et al 2007;Vendeix et al 2008). Results from NMR studies of mononucleoside 59-phosphates had indicated that the mnm 5 -modification formed a hydrogen bond to the nucleotide's 59-phosphate and that this additional bond stabilized the ribose C39-endo sugar pucker.…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular dynamics modeling and NMR spectrometry experiments had indicated that lengthy modifications at position-5 of U's could freeze the conformation of the nucleotide and dictate the hydrogen bonding geometry Durant et al 2005;McCrate et al 2006;Weixlbaumer et al 2007;Vendeix et al 2008). Results from NMR studies of mononucleoside 59-phosphates had indicated that the mnm 5 -modification formed a hydrogen bond to the nucleotide's 59-phosphate and that this additional bond stabilized the ribose C39-endo sugar pucker.…”
Section: Discussionmentioning
confidence: 99%
“…The final data are an average of the 10 scans (Figure 5B). The molecular dynamics simulation (MDS) were performed by following standard published protocol (23) with the exception of using a truncated octahedral TIP3P water box (24).
Figure 5.Thermal denaturations and circular dichroism spectra of the -Ψ 27 and the -Ψ 27 ;f 5 C 34 .
…”
Section: Methodsmentioning
confidence: 99%
“…All systems were treated with periodic boundary conditions, and the equilibration protocol of Cheatham and Kollman 103 was performed similar to previous nucleic acid simulations. 85,104 Trajectories were propagated with a 2.0-fs time step with statistics collected every 1.0 ps. Equilibration times were established for the Rev-RRE, RSG 1.2-RRE IIB, and Rev-RRE complexes under different salt concentrations before statistics were collected over 10.0 ns production runs ( Table 1).…”
Section: Simulationsmentioning
confidence: 99%